METHODOLOGICAL WAYS TO IMPROVE THE USE OF GAME-BASED TECHNOLOGIES IN TEACHING THE RUSSIAN LANGUAGE IN SECONDARY SCHOOL (World Bulletin of Education and Learning, 2026)
This thesis explores the theoretical foundations and methodological potential of using didactic games in teaching Russian as a second language. Based on the author's personal observations and scientific findings, the study analyzes the role of gaming technologies in developing students' speech and communication skills. It further examines the classification of didactic games and their significance in creating an artificial language environment.
Keywords: Communicative competence, didactic games, language games, role-playing and creative games, interactive learning, artificial language environment, secondary school.